State-private sector-civil-society partnerships and the United Nations Economic Commission for Africa (ECA) : a South African response - Ngwenya, Nomfundo Xenia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2001